Violence against new graduated nurses in clinical settings: A qualitative study. (September 2017) - Ebrahimi, Hossein; Hassankhani, Hadi; Negarandeh, Reza; Jeffrey, Carol; Azizi, Azim
Background: Ethical studies in nursing are very important topics, and it is particularly crucial with vulnerable populations such as new graduated nurses. Neglecting ethical principles and violence toward graduates can lead to their occupational burnout, job dissatisfaction, and leaving the nursing profession. Objective: This study was designed with the aim of understanding the experience of Iranian experienced nurses' use of lateral and horizontal violence against new graduated nurses. Research design: This qualitative study used a conventional content analysis approach; it was conducted with 18 experienced nurses. Data were collected through unstructured and semi-structured interviews of various general hospital departments in northwest of Iran and analyzed using methods as described by Graneheim and Lundman. Ethical considerations: This study was approved by the Regional Committee of Medical Research Ethics. The ethical principles of voluntary participation, anonymity, and confidentiality were considered. Findings: "Psychological violence, " "Verbal violence, " "Physical violence, " and "Source of violence" were four categories extracted through data analysis. Discussion: Violence behaviors are instances of workplace maltreatment that damage individual nurses, quality of care, and the ethical climate of the healthcare settings. The lateral and hierarchical violence in nursing were explained by oppressed group model. Conclusion: This study provided the context for identifying details of various types of workplace violence against new graduated nurses. It should be approached as a health system priority that requires specific multi-dimensional methods to manage consisting of identification, strategic planning, policymaking, prevention, education, and research.